Connect with knowledgeable individuals and find the best answers at IDNLearn.com. Find accurate and detailed answers to your questions from our experienced and dedicated community members.

4. Factor the polynomial.

Factor [tex]3x^2 - 7x - 6[/tex]

\begin{tabular}{|l|l|l|l|}
\hline
\begin{tabular}{l}
Factors of [tex]$a$[/tex] \\
(first terms)
\end{tabular} & \begin{tabular}{l}
Factors of [tex]$c$[/tex] \\
(last terms)
\end{tabular} & Possible factorization & \begin{tabular}{c}
Product \\
[tex]$(F \times O \times I \times L)$[/tex]
\end{tabular} \\
\hline
3, 1 & -6, 1 & [tex]$(3x + 1)(x - 6)$[/tex] & [tex]$3x^2 - 17x - 6$[/tex] \\
\hline
3, 1 & 2, -3 & [tex]$(3x + 2)(x - 3)$[/tex] & [tex]$3x^2 - 7x - 6$[/tex] \\
\hline
-3, 1 & 6, -1 & [tex]$(-3x + 6)(x - 1)$[/tex] & [tex]$-3x^2 + 9x - 6$[/tex] \\
\hline
-3, 1 & -2, 3 & [tex]$(-3x - 2)(x + 3)$[/tex] & [tex]$-3x^2 - 7x - 6$[/tex] \\
\hline
\end{tabular}


Sagot :

Certainly! Let's factor the polynomial [tex]\(3x^2 - 7x - 6\)[/tex] in a step-by-step manner.

1. Identify the coefficients:
- [tex]\(a = 3\)[/tex] (coefficient of [tex]\(x^2\)[/tex])
- [tex]\(b = -7\)[/tex] (coefficient of [tex]\(x\)[/tex])
- [tex]\(c = -6\)[/tex] (constant term)

2. Calculate the discriminant [tex]\(D\)[/tex] to check if the polynomial can be factored:
[tex]\[ \text{Discriminant}, D = b^2 - 4ac = (-7)^2 - 4 \cdot 3 \cdot (-6) = 49 + 72 = 121 \][/tex]
Since [tex]\(D > 0\)[/tex], the polynomial has two distinct real roots, so it can be factored over the real numbers.

3. Find the roots of the quadratic equation [tex]\(3x^2 - 7x - 6 = 0\)[/tex]:
The roots are given by the quadratic formula:
[tex]\[ x = \frac{-b \pm \sqrt{D}}{2a} = \frac{7 \pm \sqrt{121}}{6} \][/tex]
Simplifying, we get:
[tex]\[ x = \frac{7 \pm 11}{6} \][/tex]
Therefore, the two roots are:
[tex]\[ x_1 = \frac{7 + 11}{6} = \frac{18}{6} = 3 \][/tex]
[tex]\[ x_2 = \frac{7 - 11}{6} = \frac{-4}{6} = -\frac{2}{3} \][/tex]

4. Express the polynomial in its factored form using the roots:
If a polynomial has roots [tex]\(x = p\)[/tex] and [tex]\(x = q\)[/tex], it can be factored as [tex]\((x - p)(x - q)\)[/tex]. For [tex]\(3x^2 - 7x - 6\)[/tex], the roots are [tex]\(3\)[/tex] and [tex]\(-\frac{2}{3}\)[/tex], so the factored form is:
[tex]\[ 3(x - 3)\left(x + \frac{2}{3}\right) \][/tex]

5. Adjust the factors to include the leading coefficient (if necessary):
Since we started with a leading coefficient different from 1, we should factor out the leading coefficient [tex]\(3\)[/tex] correctly:
[tex]\[ 3x^2 - 7x - 6 = 3\left(x - 3\right)\left(x + \frac{2}{3}\right) \][/tex]

However, it's neater to express with integer coefficients:
[tex]\[ 3(x - 3)(3x + 2) \][/tex]

Thus, the polynomial [tex]\(3x^2 - 7x - 6\)[/tex] can be factored as:
[tex]\[ (3x + 2)(x - 3) \][/tex]